Chest ultrasonography in health surveillance of asbestos-related lung diseases. (June 2017) - Smargiassi, Andrea; Pasciuto, Giuliana; Pedicelli, Ilaria; Lo Greco, Erminia; Calvello, Mariarosaria; Inchingolo, Riccardo; Schifino, Gioacchino; Capoluongo, Patrizio; Patriciello, Pasquale; Manno, Maurizio; Cirillo, Alfonso; Corbo, Giuseppe Maria; et al.
Objectives: Exposure to asbestos fibers can lead to different lung diseases, such as pleural thickening and effusion, asbestosis, mesothelioma, and lung cancer. These diseases are expected to peak in the next few years. The aim of the study was to validate ultrasonography (US) as a diagnostic tool in the management of lung diseases in subjects with a history of occupational exposure to asbestos. Methods: Fifty-nine retired male workers previously exposed to asbestos were enrolled in the study. Chest US was performed in all the subjects. The US operator was blinded to earlier performed computed tomography (CT) scan reports and images. The sonographic pathological findings were pleural thickening (with or without calcifications), peripheral lung consolidation, and focal sonographic interstitial syndrome and diffuse pneumogenic sonographic interstitial syndrome (pulmonary asbestosis). Significant US findings were recorded, stored, and subsequently compared with CT scans. Results: With some patients falling into more than one category, on CT scan, pleural thickening was reported in 33 cases (56%, 26 with calcifications), focal interstitial peripheral alterations in 23 (39%), asbestosis in 6 (10%), and peripheral lung consolidation in 13 cases (22%). Comparing each pathological condition to CT scan reports, US findings had high levels of sensitivity, specificity, positive, and negative predictive values. US did not prove effective for the detection of central lung nodules or diaphragmatic pleural thickenings. Chest US was considered to be the best technique to detect minimal pleural effusions (six subjects, 10%). Conclusions: Chest US might be considered an additional tool to follow up subjects occupationally exposed to asbestos who have already undergone CT scan examination and whose pathology is detectable by US as well.